2010
DOI: 10.1352/1934-9556-48.4.278
|View full text |Cite
|
Sign up to set email alerts
|

Public Attitudes Toward People With Intellectual Disabilities: A Cross-Cultural Study

Abstract: This study investigated attitudes toward people with intellectual disabilities among the general Hong Kong Chinese population and compared these to a White British sample, using the Community Living Attitudes Scale-Mental Retardation form (CLAS-MR; D. Henry, C. Keys, F. Balcazar, & D. Jopp, 1996 ). As predicted, attitudes among the Hong Kong Chinese public (n = 149) were less favorable than the British sample (n = 135). The former were less opposed to the exclusion of people with intellectual disabilities, les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 22 publications
(31 reference statements)
3
41
1
3
Order By: Relevance
“…A study done in Palestine (Opdal, Wormnaes, and Habayeb 2001), a territory with a difficult socio-political situation and limited educational resources, showed that support for inclusion of children with intellectual disabilities was considerably lower than support for inclusion of children with other disabilities. The stigmatising views of intellectual disability that were found in a cross-cultural study by Scior et al (2010) were interpreted as reflecting 'cultural values that privilege community and interdependence over individual needs and autonomy', showing the influence that policies and culture have on attitudes.…”
Section: Child-related Factorsmentioning
confidence: 99%
“…A study done in Palestine (Opdal, Wormnaes, and Habayeb 2001), a territory with a difficult socio-political situation and limited educational resources, showed that support for inclusion of children with intellectual disabilities was considerably lower than support for inclusion of children with other disabilities. The stigmatising views of intellectual disability that were found in a cross-cultural study by Scior et al (2010) were interpreted as reflecting 'cultural values that privilege community and interdependence over individual needs and autonomy', showing the influence that policies and culture have on attitudes.…”
Section: Child-related Factorsmentioning
confidence: 99%
“…Several researchers have tried to determine the influences cultures exert on attitudes (similarities and differences) by assessing their effect(s) on individuals' behaviour (Kagawa-Singer, 2004;El-Keshky & Emam, 2015;Fatimilehin & Nadirshaw, 1994;Florian, 1982;Gaad, 2004;Scior, Kan, McLoughlin, & Sheridan, 2010). Some of these studies have shown that there were more positive attitudes towards people with ID in the developed countries than in the developing ones, other studies tend to find more positive attitudes towards people with ID in western countries than in eastern ones (Florian, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have investigated influences of cultures on attitudes towards individuals with disabilities in general and reported that (a) attitudes towards individuals with disabilities were more positive in developed countries than those in the developing countries and (b) societies characterised by values of individualism have more favourable attitudes towards individuals with disabilities than societies characterised by values of collectivism (Benomir, Nicolson, and Beail 2016;Black, Mrasek, and Ballinger 2003;El-Keshky and Emam 2015;Rao et al 2010;Scior et al 2010). …”
Section: Early Childhood Education In Turkey and The Usamentioning
confidence: 99%